ANTHROPOGENIC DRIVERS OF RELATIVE SEA-LEVEL RISE IN THE MEKONG DELTA – A REVIEW - Parker, Albert (Quaestiones Geographicae, 2020)
The Mekong Delta is sinking and shrinking. This is because of the absolute sea-level rise, and because of the subsidence of the land. The absolute sea-level rise originates from the thermal expansion of the ocean waters and the melting of ice on land, plus other factors including changes in winds and ocean circulation patterns. The subsidence originates from the construction of dams in the river basin upstream of the Delta, that has dramatically reduced the flow of water and sediments, and excessive groundwater withdrawal, plus other factors including riverbed mining, infrastructural extension, and urbanization. The origin of alluvial delta created by a continuous supply of water and sediments and the natural subsidence of uncompacted soils is relevant background information to understand the current trends. Another factor affecting the sinking and shrinking include the degradation of the coastal mangrove belt. It is concluded that the subsidence due to the reduced flow of sediments and water, and the withdrawal of groundwater more than the replenishment of aquifers is more than one order of magnitude larger than the absolute sea-level rise estimated by satellite and climate models, or the value estimated from tide gauges, that is much less. The current sinking and shrinking trends are not sustainable, as the low-lying Delta may disappear before the end of this century.